2016
DOI: 10.1002/cssc.201600933
|View full text |Cite
|
Sign up to set email alerts
|

100 °C Thermal Stability of Printable Perovskite Solar Cells Using Porous Carbon Counter Electrodes

Abstract: Many efforts have been made towards improving perovskite (PVK) solar cell stability, but their thermal stability, particularly at 85 °C (IEC 61646 climate chamber tests), remains a challenge. Outdoors, the installed solar cell temperature can reach up to 85 °C, especially in desert regions, providing sufficient motivation to study the effect of temperature stress at or above this temperature (e.g., 100 °C) to confirm the commercial viability of PVK solar cells for industrial companies. In this work, a three-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 27 publications
0
90
0
Order By: Relevance
“…46 The research of such high stable perovskite solar cells will be accelerated for commercial application.…”
mentioning
confidence: 99%
“…46 The research of such high stable perovskite solar cells will be accelerated for commercial application.…”
mentioning
confidence: 99%
“…Ito et al demonstrated that by using side‐sealing UV‐curable encapsulation together with mesoporous carbon counter electrode, the device can get rid of the penetration of ambient moisture as well as the degradation caused by UV light …”
Section: Carbon‐based Electrodesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Energy can be generated directly at hydropower plants using water's gravitational potential. [1][2][3][4][5][6][7][8][9] Energy can be generated directly at hydropower plants using water's gravitational potential.…”
Section: Introductionmentioning
confidence: 99%
“…Water can be split, through external energy like photon etc, for the generation of hydrogen and oxygen which are eventually used as the fuels in polymer electrolyte membrane fuel cells. [1][2][3] Similarly, the requirement of electrostatic separator, electrocatalysts for oxidation and reduction processes, and the stability of the electrolytes are key issues in metal-air batteries. [10][11][12] However, the requirement of an external energy for the water splitting along with a catalyst, durability and poisoning of the catalyst, cost effectiveness, fuel storage and its transport, etc limits such applications.…”
Section: Introductionmentioning
confidence: 99%